2017
DOI: 10.1371/journal.pone.0173706
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of H3K9 methyltransferase G9a ameliorates methylglyoxal-induced peritoneal fibrosis

Abstract: Activity of H3K9 histone methyltransferase G9a is reportedly induced by transforming growth factor-β1 (TGF-β1) and plays an important role in the progression of cancer and fibrosis. In this study, we investigated whether inhibition of G9a-mediated H3K9 methylation attenuates peritoneal fibrosis in mice and human peritoneal mesothelial cells (HPMCs). Nonadherent cells of peritoneal dialysis (PD) patients were isolated from PD effluent to examine expression of G9a. Peritoneal fibrosis was induced by peritoneal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…In this study, inhibition of SET7/9 suppressed peritoneal fibrosis without changing TGF-β1 expression in MGO-injected mice. Since our previous studies showed that TGF-β1 is co-expressed with inflammatory cells in a mouse model of MGO-induced peritoneal fibrosis [ 39 ], the present data imply that H3K4me1 does not affect inflammation.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…In this study, inhibition of SET7/9 suppressed peritoneal fibrosis without changing TGF-β1 expression in MGO-injected mice. Since our previous studies showed that TGF-β1 is co-expressed with inflammatory cells in a mouse model of MGO-induced peritoneal fibrosis [ 39 ], the present data imply that H3K4me1 does not affect inflammation.…”
Section: Discussionsupporting
confidence: 48%
“…Yang et al also reported that C646, a histone acetyltransferase inhibitor attenuates peritoneal fibrosis by blocking the TGF-β1/Smad3 signaling pathway [ 38 ]. Furthermore, we previously showed that the H3K9 methyltransferase G9a is implicated in peritoneal fibrosis [ 39 ]. These findings suggest that histone modification could be a therapeutic target during peritoneal fibrosis development.…”
Section: Discussionmentioning
confidence: 99%
“…These pro-fibrotic changes both in vitro and in vivo were abrogated by application of the selective G9a-methyltransferase inhibitor BIX01294, with a reduction in repressive H3K9me1 levels (145). Similar therapeutic benefit through H3K9me1 suppression by G9a-methyltransferase inhibition has been also recently described in an in vitro model of peritoneal fibrosis (201). Involvement of G9a in gene repression has also been reported in pulmonary fibrosis through H3K9 trimethylation of the anti-fibrogenic cyclooxygenase-2 (COX2) gene promoter (69).…”
Section: Histone Methylation In Fibroblastsmentioning
confidence: 54%
“…Consistent with these observations, bleomycin-treated lungs showed a significant increase in hydroxyproline content, which was partially but not significantly reduced in the lungs of BIX01294-treated mice ( Figure 8G). These latest observations, while failing to reach statistical significance, are supported by recent papers reporting the beneficial effects of BIX01294 in mouse models of kidney and peritoneal fibrosis (60,61).…”
Section: Inhibition Of G9a Restores Ppargc1a Gene Expression In Vivo mentioning
confidence: 92%